Icodextrinový peritoneální dialyzacní roztok v klinické praxi - Opatrná, S (Vnitrni lekarstvi, 2008)
Icodextrin, a glucose polymer, is an alternative osmotic agent to glucose in peritoneal dialysis solutions. Icodextrin generates ultrafiltration through colloid osmosis and is thus effective even during long-term (e.g., nighttime) dwells and in cases of high peritoneal permeability, where it prevents dialysate reabsorption into the systemic circulation. Ultrafiltration is maintained even in the presence of peritonitis. The incidence of bacterial peritonitis is not different when using icodextrin- or glucose-based solutions. Some time ago, icodextrin use was implicated in an increased incidence of sterile peritonitis. This was due to contamination of some batches of the solution by peptidoglycan present in the cell wall of G+ bacteria. Using exact isotope methods, treatment with icodextrin-based solution has been shown to improve the hydration status of peritoneal dialysis patients, suggesting a potential for improved blood pressure control. Icodextrin-based dialysis is associated with a reduction of left ventricular mass. Given the methodological flaws of trials conducted to date, the acute hemodynamic effects of icodextrin cannot be conclusively interpreted. Inclusion of icodextrin-based solution instead of the glucose-based one into the prescription of peritoneal dialysis decreases the metabolic load with glucose potentially having a beneficial effect on hyperlipidemia, hyperinsulinemia and hyperleptinemia, with improved glycemic control in patients with diabetes as an additional benefit. Function of the peritoneum as a dialysis membrane is stable during icodextrin-based treatment, possibly longer compared with glucose-based solutions. Data derived from a large-scale registry have shown lower mortality oficodextrin-treated patients; this, however, needs to be confirmed by prospective randomized controlled trials.
Keywords: Icodextrin; Water-Electrolyte Balance; Humans; hemodialyzační roztoky; Hemodialysis Solutions; peritoneální dialýza; lidé; ultrafiltrace; glukosa; Glucans; Peritoneal Dialysis; peritoneum; icodextrin; Ultrafiltration; Glucose; peritonitida; vodní a elektrolytová rovnováha; Peritoneum; glukany; hemodynamika; Peritonitis; Hemodynamics